In silico design of mimosine containing peptides as new efficient chelators of aluminum. Issue 14 (7th March 2019) - Mujika, J. I.; Dalla Torre, G.; Lachowicz, J. I.; Lopez, X.
Abstract : A novel chelator of aluminum is presented, a peptide containing three mimosine residues. Abstract : The design of new and efficient chelators that can remove aluminium(iii ), a metal with increasing recognition as a potential toxic agent, from biological systems is an area of high therapeutic relevance. In the present paper, we present an extensive computational study of a new promising type of these chelators based on mimosine containing peptides. The reason to choose mimosine is that the sidechain of this residue is similar to deferiprone, a ligand known to tightly interact with highly-valent metals, and in particular with Al(iii ). In this article we analyze systematically, using a combination of methods that include QM/MM MD simulations, how the size and sequence of the polypeptides can alter the fundamental binding patterns to aluminum, in comparison with the binding to deferiprone. Particular attention is given towards the identification of the smallest peptide that interacts efficiently with aluminum, since polypeptide size is a fundamental factor to allow a given polypeptide to efficiently cross the cell membrane. The results indicate that the longest peptides, with 8 or 9 amino acids, show no difficulties interacting with Al(iii ) in an optimum arrangement. By contrast, when the peptide contains five or six amino acids Al(iii ) is pentacoordinated, reducing the stability of the resultant complex. In summary, our study demonstrates that the mimosine containing peptides can efficiently coordinate highly valent metals such as Al(iii ), with a subtle dependence of the binding on the specific chain-lengths of the polypeptide. We believe that the present study sheds light on the adequacy of this new type of chelator towards aluminum binding.